High‐Temperature Na2SO4 Deposit‐Assisted Corrosion of Silicon Carbide – I: Temperature and Time Dependence. Issue 4 (26th December 2014) - Hagan, Joseph M.; Opila, Elizabeth J.; Parthasar, T.
<x xml:space="preserve">Abstract</x> Time and temperature dependence of Na2SO4‐induced hot corrosion were studied for sintered‐α (Hexoloy) as well as CVD‐SiC at temperatures between 900°C and 1100°C and at times from 0.75 to 96 h. The extent of corrosion was quantified using mass change measurements, removal of corrosion products using sequential water, HCl, and HF dissolution steps followed by ICP‐OES analysis, and by optical profilometry of corroded materials to characterize pitting on the sample surface. In addition, SEM, EDS, and XRD were used to better understand the morphology, distribution, and phase composition of corrosion products. It was found that hot corrosion of Hexoloy was more severe than that of high‐purity CVD‐SiC. Hot corrosion is initially rapid until a continuous silica layer is formed underneath the mixed silicate layer. Once a continuous silica layer was formed the temperature dependence of the corrosion rate was consistent with diffusion of oxygen through the silica layer.